Investigation of Different Windshield Designs for Aerodynamic Drag Force in Motorcycle - Ghazali, Farid; Abdul Ghafir , Mohammad Fahmi (Progress in Aerospace and Aviation Technology, 2024)
This research investigates the aerodynamic performance of different windshield designs for the Honda CB500X motorcycle at 140 km/h, focusing on drag force, drag coefficient, and pressure distribution. Three aftermarket windshields and one original equipment manufacturer (OEM) windshield were developed in SolidWorks and simulated using computational fluid dynamics (CFD) in ANSYS Fluent. The OEM windshield outperformed the aftermarket designs in terms of aerodynamic efficiency, with a lower drag force (735.65991 N) and drag coefficient (0.3951). However, a pressure distribution study found that aftermarket windshields provided better deflection of airflow, resulting in less direct wind effect on the rider, potentially improving rider comfort and safety. These findings highlight the trade-off between aerodynamic efficiency and rider comfort in windshield design.